Gambaran Karakteristik Persalinan Spontan (Spontaneous Vertex Delivery) di Wilayah Kecamatan Nisam Aceh Utara Tahun 2021 - Salmiah Salmiah; Nora Maulina; Iskandar Albin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Labor is a process that requires great energy and stamina, during this process the cervix will open and become thinner, making it easier for the fetus to descend into the birth canal. During labor, additional sources of energy from outside the body are needed to conserve glycogen stores during labor. Lack of nutritional intake during labor can reduce blood glucose levels so that the mother experiences muscle fatigue, characterized by high levels of lactate in the blood and inadequate uterine contractions which results in delayed progress or delayed delivery. The research method is descriptive observational with a population of 421 deliveries in Nisam District. The sample taken is part of the population. Research variables are maternal age at delivery, education, parity, distance of residence, occupation, socio-economic and birth attendant. The results of this study were from 81 deliveries that occurred in Nisam District in 2021, the mother's age at delivery was 20-35 years (93.8%), high school education (54.3%), Primipara parity (50.6%), distance of residence <15 minutes (69.1% ), non-civil servant occupation (86.4%), socio-economic minimum wage (53.1%), birth attendant assisted by a midwife (100%). The conclusion of this study is the characteristics of spontaneous delivery in Nisam District in 2021, namely; The highest maternal age at delivery was 20-35 years, the most education was high school, the most parity was primipara, the most residence distance was <15 minutes, the most occupations were Non-PNS, most socio-economically above the minimum wage, and spontaneous birth attendants by midwives.